THE INFLUENCE OF PROFITABILITY, SALES GROWTH, FIRM SIZE, AND BUSINESS RISK ON CAPITAL STRUCTURE - Mila Rosita; Ni Ketut Purnawati (CV. Adiba Aisha Amira, 2025)
Capital structure plays a crucial role in a company’s financial framework, as it can significantly influence the firm’s financial condition and stock price. Several factors may affect capital structure, including profitability, sales growth, firm size, and business risk. This study aims to analyze the influence of profitability, sales growth, firm size, and business risk on the capital structure of companies in the chemical, pharmaceutical, and medicine sub-sectors listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The research employs both descriptive and inferential analysis methods, using multiple linear regression tests. The study population consists of 11 companies, with 8 companies selected as samples through purposive sampling. The data used are secondary data obtained from annual financial reports accessed via the official IDX website (www.idx.co.id). The results indicate that profitability has a significant negative effect on capital structure, sales growth has a significant positive effect, firm size has not significant effect, and business risk has a significant negative effect on capital structure.